2020
DOI: 10.3390/plants9040468
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Breeding for MLN Resistance: Heterosis, Combining Ability, and Hybrid Prediction

Abstract: Prior knowledge on heterosis and quantitative genetic parameters on maize lethal necrosis (MLN) can help the breeders to develop numerous resistant or tolerant hybrids with optimum resources. Our objectives were to (1) estimate the quantitative genetic parameters for MLN disease severity, (2) investigate the efficiency of the prediction of hybrid performance based on parental per se and general combining ability (GCA) effects, and (3) examine the potential of hybrid prediction for MLN resistance or tolerance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
4
14
0
3
Order By: Relevance
“…A significant genotype, genotype by environment interaction variances, and moderate to high broad-sense heritability were observed for GY and other related traits AD, ASI, PH, EH, TLB, MOI, and GLS measured under WW and WS conditions similar with the results reported by Yuan et al [ 24 ]. MLN-DS and AUDPC were highly heritable with 0.67 and 0.74, respectively, which is consistent with earlier reported studies [ 31 , 37 , 53 , 54 ]. Several genotypes have been evaluated by CIMMYT against MLN disease in search for resistant materials [ 12 , 24 , 31 , 32 , 38 , 55 ]; with the current study, we identified about 52 MLN disease resistant/tolerant genotypes while most of other genotypes were susceptible.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A significant genotype, genotype by environment interaction variances, and moderate to high broad-sense heritability were observed for GY and other related traits AD, ASI, PH, EH, TLB, MOI, and GLS measured under WW and WS conditions similar with the results reported by Yuan et al [ 24 ]. MLN-DS and AUDPC were highly heritable with 0.67 and 0.74, respectively, which is consistent with earlier reported studies [ 31 , 37 , 53 , 54 ]. Several genotypes have been evaluated by CIMMYT against MLN disease in search for resistant materials [ 12 , 24 , 31 , 32 , 38 , 55 ]; with the current study, we identified about 52 MLN disease resistant/tolerant genotypes while most of other genotypes were susceptible.…”
Section: Discussionsupporting
confidence: 92%
“…CIMMYT in collaboration with national research institutions has developed resistance breeding strategies against MLN. A large number of maize genotypes were screened, and MLN disease-resistant source materials and resistance QTLs were identified to develop resistant varieties by integrating both conventional and molecular breeding techniques [ 12 , 31 , 37 , 38 ]. Nevertheless, searching additional MLN disease-resistant lines, evaluation of the genotype’s performance, identification and validation of QTLs associated with the target disease, GY, and other related traits play a vital role in the development of MLN disease-resistant varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eggplant, GD assessed through SNPs showed a diminutive correlation with the hybrid means, heterosis, and SCA values [27]. In a previous study of maize lethal necrosis, a very low and negative correlation was observed between parental lines marker-based genetic distance and heterosis [31].…”
Section: Plant Heterosis Prediction Based On Genetic Distancementioning
confidence: 75%
“…Натепер особливості збудників вірусних, бактеріальних та грибкових захворювань, механізм взаємодії з організмом-хазяїном та стійкість до хвороб у кукурудзи інтенсивно вивчаються на молекулярному рівні (Wu et al, 2017;Ge et al, 2020;Nyaga et al, 2020;Ali et al, 2021). Серед них значна увага приділяється сажковим хворобам (Schirawski et al, 2010;Di et al, 2017;Zuo et al, 2019).…”
Section: вступunclassified